Impact Of Agricultural Production on Stunting Prevalence in Central Java Province - Maria; Tinjung Mary Prihtanti; Esther Sheliena; Yuliawati; Damara Dinda Nirmalasari Zebua (Jurnal Penelitian Pendidikan IPA, 2025)
Stunting is a chronic nutritional problem that impairs children's growth and development. This study aims to examine the influence of agricultural production and food access indicators on stunting prevalence across 35 districts and cities in Central Java Province from 2021 to 2023. The independent variables include rice production, horticultural production, broiler chicken production, cow milk production, egg price index, and paddy field area. Panel data regression using a fixed effects model (FEM) was selected as the most appropriate analytical approach, based on the results of the Chow and Hausman tests. The results show that rice production, egg price index, and paddy field area have a statistically significant influence on stunting prevalence. In contrast, horticultural production, broiler chicken production, and cow milk production do not show significant effects. These results suggest that improving food availability alone is not sufficient; it must be accompanied by enhanced access and affordability. The study highlights the importance of localized agricultural and nutritional strategies in reducing stunting. Analysis indicates the decline in stunting prevalence in Central Java, although several areas still record high rates. Rice production, paddy field area, and egg prices index as significant factors influence stunting, highlighting the need for integrated policies that combine agricultural development with improved access, affordability, and nutrition education.